2021
DOI: 10.1007/s12072-021-10212-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of FGF19/FGFR cascade improves antitumor immunity and response rate in hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is the most common liver cancer globally, claiming nearly 1 million lives each year. Overexpression of broblast growth factor (FGF) receptors (FGFRs) signaling cascade has been shown to contribute to tumorigenesis, metastasis, and poor prognosis in HCC. Therefore, targeted inhibition of the FGF/FGFR cascade may represent a new treatment strategy for HCC patients. MethodsHCC patient-derived xenograft (PDX) models were implanted into either severe combined immunode cient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…FGF401 is one of the promising reversible FGFR4 inhibitor, which may have improved effects over irreversible inhibitors [ 36 ]. In a preclinical study, FGF401 was studied in combination with FGFR1–3 inhibitor, infigratinib, and found that HCC patients with high expression of FGFR2/3 or FGF19/FGFR4 might benefit from the combination if evaluated further in the clinical studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF401 is one of the promising reversible FGFR4 inhibitor, which may have improved effects over irreversible inhibitors [ 36 ]. In a preclinical study, FGF401 was studied in combination with FGFR1–3 inhibitor, infigratinib, and found that HCC patients with high expression of FGFR2/3 or FGF19/FGFR4 might benefit from the combination if evaluated further in the clinical studies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…FGF19 is a dietary-responsive endocrine hormone essential for enterohepatic circulation of BAs 13 . Abnormal expression of FGF19-FGFR4 has been shown to accelerate hepatocarcinogenesis and metastasis, while inhibition of the FGF19/FGFR pathway augments tumor-suppressive activity and improves the prognosis in patients with HCC 14 , 15 . In summary, the role of BAGs in hepatic carcinogenesis and prognosis is variable and worthy of further research.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that FGF genes were ubiquitously expressed in different tissues and developmental stages with divergent expressions, suggesting that FGFs are widely involved in various biological processes and perform multiple biological functions in S. schlegelii , as reported in mammals. For instance, FGF19 , was found to be specifically expressed in the liver of S. schlegelii , implying that it may be involved in liver physiological function, including glycogen metabolism [ 34 ], lipid metabolism [ 35 ], and immune response [ 36 ], as demonstrated in mammals. In zebrafish, FGF signaling has also been widely verified to play a key role in liver homeostasis regulation and specification [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%